ILLEGAL LOGGING ENFORCEMENT: DYNAMICS OF PENAL SANCTIONS IN KEBUMEN COURT - Budiyono, Budiyono; Lirëza, Linert (Diponegoro Law Review, 2024)
This research investigates the multifaceted nature of criminal punishment, considering its purposes such as deterrence, retribution, rehabilitation, and the maintenance of societal order. Specifically focusing on Article 78, paragraph 15 of forestry law, which delineates penal sanctions, the study explores the application of confiscatory penalties in cases of forestry offenses, particularly illegal logging. The research centers on the practices of the Kebumen District Court in enforcing sanctions against illicit logging, examining the discretionary powers exercised by judges. Despite the existence of the 2005 Judicial and Court Management Technical Instructions governing evidence seizure in illegal logging cases which constrain judicial authority in sentencing. Adopting a non doctrinal research through interview to the judges and literature research as data collection. Those data are analysed qualitatively. the study reveals intricate challenges in penalty enforcement at the Kebumen District Court, encompassing imprisonment, fines, and the confiscation of forest products. Notably, disagreements among judges regarding adherence to Supreme Court guidelines highlight the complexities of balancing judicial autonomy with technical directives. The findings underscore the need for clarifying legal frameworks and enhancing judicial training to harmonize the application of penalties in forestry crime cases, thereby ensuring consistency and fairness in sentencing practices.